PERANAN KOMUNIKASI DALAM KEPEMIMPINAN PEMERINTAHAN DAN PARTISIPASI MASYARAKAT - Linda Christine S. Paembonan (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2011)
AbstractThe role of communication in the government’s leadership in an attempt to influence,move, guide and direct its community or follower is a very important factor for therealization of the goals set. Government leaders as a mover and a good communicator willclarify perceptions and convince his followers to engage and active participate in thedevelopment activities; all at once as a proof that government is practicing the communitybaseddevelopment or it is so called development from, by and for the people.Keywords: Communication role, Government leadership, Community-based development.